Dragon age : deception - DeFilippis, Nunzio; Weir, Christina (Dark Horse Books, 2019)
"Olivia Pryde hasn't worked an honest day in years. Once an actress, she now lives by the con, and has come to Tevinter with a new target: Calix Qintara, the heir to a wealthy house. Once she approaches the young man, she quickly realizes that he is not exactly who he says he is--and she may be in too deep."--